If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y/9+6=-8
We move all terms to the left:
y/9+6-(-8)=0
We add all the numbers together, and all the variables
y/9+14=0
We multiply all the terms by the denominator
y+14*9=0
We add all the numbers together, and all the variables
y+126=0
We move all terms containing y to the left, all other terms to the right
y=-126
| 4x-17x-8=0 | | 7(6x-3)=(5x-4) | | 7n-8n+8=n+4 | | X/7+x/5=12 | | 5v+2v+2=-12 | | 1.2x+13-8.7x=50.5 | | 2/3(x+4)=1/3(x+12) | | 1÷3=20÷d | | 4/9d+1/9=2/3 | | 4x-3(×-2)=21 | | 1.2x+13-8.7=50.5 | | 6x2+11x=2 | | 4(x-3)=-16;-1 | | 2x=1-(2-x)^1/2 | | 400=2x+2(2/3x) | | 3m=2m+3 | | 7x+6(7x+27)=-181 | | -3x+1=3+2x | | -19+4x-23=-2 | | 3=7–2s | | j+9=15 | | -2(2x-6)=-4(2x-10) | | 5/7x=23/14 | | 5(5t+1)=25t-7 | | 2t-3+t=30 | | (x-3)/7=(x+5)/6 | | --4/7=-2f/3 | | 2^2x=64 | | 4+2p=10(3-5p-2) | | -2(4a-3)=30 | | v+27=10v | | 4x=-8x-28 |